1992
DOI: 10.1007/bf01309578
|View full text |Cite
|
Sign up to set email alerts
|

Androstenediol regulates systemic resistance against lethal infections in mice

Abstract: We previously reported that subcutaneous injection of DHEA (5-androsten-3 beta-ol-17-one, dehydroepiandrosterone) protected mice from lethal infection. This included both a lethal herpes virus type 2 encephalitis and a lethal systemic coxsackievirus B4 (CB4) infection. Androstenediol (5-androsten-3 beta-17 beta-diol, AED), a metabolic product of DHEA is up to 100 x more effective in regulating systemic resistance against lethal infection with CB 4 than its precursor DHEA. Compared to DHEA, treatment with AED w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Moreover, ADIOL TAGAWA et al has been reported to be a more biologically active metabolite than dehydroepiandrosterone (DHEA). For example, ADIOL was at least 100-fold more effective in up-regulating systemic resistance against Coxsackie virus infection [7,8].…”
Section: Adiols) Focused On Its Role As An Intermediate In Sex Steroimentioning
confidence: 99%
“…Moreover, ADIOL TAGAWA et al has been reported to be a more biologically active metabolite than dehydroepiandrosterone (DHEA). For example, ADIOL was at least 100-fold more effective in up-regulating systemic resistance against Coxsackie virus infection [7,8].…”
Section: Adiols) Focused On Its Role As An Intermediate In Sex Steroimentioning
confidence: 99%
“…Based on animal examination, it appeared that DHEA was converted in vivo, and we assumed that ␤ AED was the active agent. Consequently, a comparison of the effects of ␤ AED and DHEA on lethal CB4 infections in C57BL/6J mice was performed [16] . The results in table 1 demonstrate that CB4 infection at a dose of 10 4 PFU per animal was lethal in 100% of the animals.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of AED are mediated by an increase in host resistance and not by a direct antibacterial or antiviral effect, and a restoration of myelopoeisis after irradiation. [6][7][8][9]26,27 The data presented in this initial report indicate that in addition to restoration from gamma radiation injury, AED also mitigates the damages from high LET charged particle radiation exposure. Since bacteria such as Pseudomonas aeruginosa and Cepacia burkholderi, as well as opportunistic species such as Streptococcus pneumoniae, have been shown to be infectious to individuals with weakened immune systems, they may be potential pathogens for crew members in space.…”
mentioning
confidence: 96%
“…Previous reports demonstrated that a single subcutaneous injection of AED protects the host from death and restores radiation-mediated destruction of the myelopoeitic system after exposure to wholebody gamma radiation dose of 8 Gy (LD100 for C57BL/6J; human LD100 6 Gy). [6][7][8][9] Gridley et al 10,11 and Pecaut et al 12,13 have reported on the acute effects of whole-body iron particle radiation to C57BL/6J mice. Four days after exposure to a dose of 3 Gy, spleen weight was reduced by 52% and white blood cell (WBC) counts, monocytes, and lymphocytes levels were reduced by about 80%.…”
mentioning
confidence: 99%
See 1 more Smart Citation